Ki Baruch Hu : Ancient Near Eastern, biblical, and Judaic studies in honor of Baruch A. Levine - Levine, Baruch A.; Chazan, Robert; Hallo, William W.; Schiffman, Lawrence H. (Eisenbrauns, 1999)
Known to most readers as author of Leviticus in the Jewish Publication Society Torah Commentary series and Numbers 1-20 in the Anchor Bible series, as well as numerous essays in Bible dictionaries and encyclopedias, Baruch Levine holds the place of honor in this collection. The volume has been compiled by the students, colleagues, and friends known to him over his many years of professorship at New York University. Included in the festschrift are 36 essays in English and 5 essays in Hebrew. --